2021
DOI: 10.1093/jn/nxaa353
|View full text |Cite
|
Sign up to set email alerts
|

Fewer Community-Acquired Colds with Daily Consumption of Lactiplantibacillus plantarum HEAL9 and Lacticaseibacillus paracasei 8700:2. A Randomized, Placebo-Controlled Clinical Trial

Abstract: Background Viral infections of the upper airways are the most common cause for absence from work or school, and there is evidence for probiotic efficacy in reducing the incidence and severity of these infections. Objectives We aimed to confirm the previously reported beneficial effects of Lactiplantibacillus plantarum HEAL9 and Lacticaseibacillus paracasei 8700:2 against community-acquired common colds and identify a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Ahrén et al reported that there was no significant difference between the study groups in the incidence and the overall number of side effects reported by children. However, more gastrointestinal side effects in the probiotic group compared to the control group seem to be explained by a higher frequency of vomiting, an AE was also reported in other studies following the administration of probiotics to young children (Ahrén et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Ahrén et al reported that there was no significant difference between the study groups in the incidence and the overall number of side effects reported by children. However, more gastrointestinal side effects in the probiotic group compared to the control group seem to be explained by a higher frequency of vomiting, an AE was also reported in other studies following the administration of probiotics to young children (Ahrén et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…The results of many studies suggest that probiotics as health supplements and treatment agents are safe (Ahrén et al, 2021). However, the side effects of probiotics should be controlled when used in a specific population.…”
Section: Discussionmentioning
confidence: 99%
“…Pearson's coefficient was r 2 = 0.06. The years with the highest number of published works were 2021 with three [22][23][24] followed by two studies each in 2019 [25,26], 2018 [27,28], 2015 [29,30], 2011 [31,32], 2010 [33,34], and 2005 [35,36]. The years with only one publication were 2016 [37], 2012 [38], and 2013 [39].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies (88%) included in the review were double-blind clinical trials with placebo and control group [22][23][24][25][26][27][28][29][31][32][33][34][35][36][37][38][39], except for Shida et al [30] without masking patients and researchers. Of these works, four were developed in Germany [22,29,33,36], three each in China [23,24,27] and the United States [32,37,38], two each in Malaysia [25,28], Japan [26,30], and Sweden [34,35], and a single study each in the countries of Denmark [29], Australia [39], and Italy [31]. All of them written in English.…”
Section: Resultsmentioning
confidence: 99%
“…There are at least 150 published clinical trials that have assessed the beneficial effect of probiotic consumption in preventing URTIs conducted on various populations. Some positive effects on various groups of adults from recent studies include significantly fewer community-acquired colds [97], significantly decreased URTI symptoms [98], significantly reduced URTI [99] and significantly fewer number of days with URTI symptoms [100].…”
Section: Discussionmentioning
confidence: 99%